Strategi Penguatan Kualitas Laporan Keuangan Masjid dan Pondok Pesantren di Indonesia - Enjang Ryan Firmansyah; Sri Rokhlinasari; Alvien Septian Haerisma (Jurnal Ilmiah Ekonomi Islam, 2026)
The purpose of this study is to examine strategies to improve the quality of financial reports for mosques and Islamic boarding schools in Indonesia. The method used is qualitative research with a library research approach. The data analysis technique used in this study is content analysis, namely by examining in depth the contents of various literature to identify concepts, patterns, and relationships between variables related to strengthening the quality of financial reports. The results indicate that several mosques and Islamic boarding schools are among the institutions that play a role in implementing Islamic economics in Indonesia. However, both institutions still face challenges in preparing financial reports. This is indicated by the presence of several mosques and Islamic boarding schools whose financial reports do not meet standards. The proposed strategy for strengthening financial report quality in this study consists of three: first, optimizing the accounting system. Second, improving the competency of human resources. Third, the need for management support.